Whistlers detected and analyzed by Automatic Whistler Detector (AWD) at low latitude Indian stations - Singh, Abhay K.; Singh, S.B.; Singh, Rajesh; Gokani, Sneha A.; Singh, Ashok K.; Siingh, Devendraa; Lichtenberger, János (My University, 2014)
Recently, at three Indian low latitude stations: Varanasi (geomag. lat. 14°55′N, geomag. long. 153°54′E, L: 1.078), Allahabad (geomag. lat. 16.05°N; geomag. long. 155.34°E, L: 1.081) and Lucknow (geomag. lat. 17.6°N, geomag. long. 154.5°E, L: 1.104) an Automatic Whistler Detector (AWD) has been installed in December, 2010 for detection and analysis of whistlers. This instrument automatically detects and collects statistical whistlers data for the investigation of whistlers generation and propagation. Large numbers of whistlers have been recorded at Varanasi and Allahabad during the year 2011 which is analyzed in the present study. Different types of whistlers have been recorded at Varanasi and Allahabad. The correlation between recorded whistlers and causative lightning strikes were analyzed using data provided by World-Wide Lightning Location Network (WWLLN). We observed that for both the stations more than 50% of causative sferics of whistlers were observed to match closely with the times of WWLLN detected lightning strikes within the propagation times of causative tweeks. All of these lightning strikes originated from the region within 500–600 km radius circle from the conjugate point of Varanasi and Allahabad supports the ducted propagation at low latitude stations. The dispersion of the observed whistlers varies between 8 and 18 s1/2, which shows that the observed whistlers have propagated in ducted mode and whole propagation path of whistlers lies in the ionosphere. The ionospheric columnar electron contents of these observed whistlers vary between 13.21 TECU and 56.57 TECU. The ionospheric parameters derived from whistler data at Varanasi compare well with the other measurements made by other techniques.
Keywords: Very low frequency waves; Whistlers; Lightning discharges; Ionospheric/plasmaspheric parameters; Magnetospheric physics; Automatic whistler detector